Echo Bay Mines Ltd.; A Company's Use Of Gold - Robert F. Calman (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1990)
OUTLINE FIVE EXAMPLES OF GOLD-LINKED FINANCINGS 1. Financing the Lupin Mine • Sale of Cdn $40.0 million of 12% preferred shares and Cdn $40.0 million of Gold Purchase Warrants @ $595 per ounce. 2. Financing the Copper Range acquisition • Borrowing 100,000 ounces from a Canadian chartered bank @ US$307 for five years. 3. Financing the Round Mountain expansion • Borrowing up to US $80.0 million in dollars, convertible into gold, repayable over five years from a group of North American banks. 4. Financing the Tenneco Precious Metals Division acquisition •Sale of SFr 110.0 million of ten year 3-718% bonds with warrants to buy 132,000 ounces of gold at US $560. 5. On Forward Sales, Puts and Calls • Gold, Silver, Canadian Dollars, Swiss Francs THE FINANCIAL RULES AT ECHO BAY 1. Never bet the company 2. Equity is the primary form of capital for a gold mining company 3. On debt 4. The Yardsticks for Corporate Decisions 5. Financial Community Relationships 6. Dividend Policy No Text Available Tables Follow